Growth, lung function, and physical activity in schoolchildren who were very-low-birth-weight preterm infants - Winck, Aline Dill (J Bras Pneumol, 2016)
OBJECTIVE: To compare somatic growth, lung function, and level of physical activity in schoolchildren who had been very-low-birth-weight preterm infants (VLBWPIs) or normal-birth-weight full-term infants. METHODS: We recruited two groups of schoolchildren between 8 and 11 years of age residing in the study catchment area: those who had been VLBWPIs (birth weight < 1,500 g); and those who had been normal-birth-weight full-term infants (controls, birth weight ≥ 2,500 g). Anthropometric and spirometric data were collected from the schoolchildren, who also completed a questionnaire regarding their physical activity. In addition, data regarding the perinatal and neonatal period were collected from the medical records of the VLBWPIs. RESULTS: Of the 93 schoolchildren screened, 48 and 45 were in the VLBWPI and control groups, respectively. No significant differences were found between the groups regarding anthropometric characteristics, nutritional status, or pulmonary function. No associations were found between perinatal/neonatal variables and lung function parameters in the VLBWPI group. Although the difference was not significant, the level of physical activity was slightly higher in the VLBWPI group than in the control group. CONCLUSIONS: Among the schoolchildren evaluated here, neither growth nor lung function appear to have been affected by prematurity birth weight, or level of physical activity.